Risk-sensitivity in a rat population under interval schedules of reinforcement : open and closed economies - Gregory, Keith Joseph (My University, 1995)
A group consisting of eight male Hooded rats was tested for risk-sensitive foraging preferences in an eight station operant arena, under conditions of open and closed economies. The group could choose to forage at either four fixed interval stations or four variable interval stations of the same mean interval value. The visual, tactile, and spatial discriminative stimuli associated with the fixed and variable stations was enhanced to assist in discriminating between the variances of the schedules associated with the stations. The following four interval values were tested, with each in effect for five consecutive days: 15, 30, 90, and 180 seconds. The open economy was defined by a 30 minute session conducted twice a day followed by a supplemental feeding at the end of each day. The closed economy consisted of continuous 2 4 hour access to the stations, with no supplemental feeding. Results revealed differential effects upon foraging choices by the two different economies. In the open economy, the group of rats were risk-indifferent in their foraging preferences, while in the closed economy the rats foraged in a manner that was contrary to risk-sensitive theory. During the closed economy the rats were risk-prone when net energetic gain was high and became less risk-prone as net energetic deficits occurred. Discussion is given on the possible influence of competition and discriminatory cues upon a rat populations foraging preferences.
Keywords: Rats Behavior; Reinforcement (Psychology)